Critical Legal Reading of World Anti-Doping Agency’s Gene Doping Guidance - Al-Dafrawi, Ahmad Saad Ahmad (Hasanuddin Law Review, 2023)
The genetic barrier negatively affected competitive athletic performance until the advent of gene therapy and genetic manipulation, which cast doubt on and impacted the legitimacy of sporting events. At that a critical point, the World Anti-Doping Agency (WADA) interfered in such experimentation and application with a serious attempt to curb the problem and set things back on track with the healthiest standards in light of bioethics. However, the major problem that the agency has encountered and which this legal study wants to raise, and address is the legal consequences that result from the lack of a reliable method that provides sufficient evidence and definitive answers to confirm whether cellular and gene doping are occurring or not. This is study aims to demonstrate that the procedures for accusing players of using genetic modification and genetic change techniques are incorrect and insufficient and may be harmful. The suspicion must be interpreted in favour of the accused (i.e., the athlete) in accordance with the general principles of penal codification. However, some of the Agency's procedures are not compatible with the provisions of international treaties, not to mention they conflict with the Punitive legislation of numerous countries.